Natural catastrophe : climate change and neoliberal governance - Elliott, Brian, 1969- (Edinburgh University Press, 2016)
Brian Elliott persuasively argues that climate change is not a natural phenomenon but a political phenomenon: a symptom of neoliberal governance. This helps us to understand how, across wealthy liberal democracies, environmental concern has increasingly been framed as a consumer responsibility issue rather than as a matter of structural social-political transformation. Thinking of a world truly beyond climate change requires us to reimagine the state beyond its current neoliberal configuration. Elliott argues that, in order to achieve this, environmental politics in the west needs to renew the Marxist challenge to the global market́⁰₉s benign production of social utility and construct a new non-apocalyptic politics of nature.